استراتيجية مدرس اللغة العربية في حل مشكلات الطلاب في الكتابة العربية - Miswarul Abdi Aziz (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
The objectives of this research are to find out the problems faced by students in Arabic writing in the state Islamic High School 4 Pidie. And to know the school's strategy in solving problems for students in Arabic writing in the state Islamic High School 4 Pidie. The research method used by the researcher in completing this research is a descriptive study. The research tools used by the researcher in collecting data are personal interview with the teacher and direct observation. The results of the research indicated that students in the state Islamic High School 4 Pidie face various problems in Arabic writing. Of which: they do not know how to convert the audible sound into visual form and do not know how to write simple sentences. The school's strategies in teaching Arabic writing are good because the school enables the use of learning strategies. However, the use of learning strategies applied by the teacher in teaching Arabic writing is compatible with the teaching materials.